2017
DOI: 10.1007/s13205-017-0832-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of in vitro digestibility of dietary microalga Chlorella vulgaris and cyanobacterium Spirulina platensis as a nutritional supplement

Abstract: Microalgal proteins are promising sources for functional nutrition and a sustainable candidate for nutraceutical formulations. They also gain importance due to emerging focus on a healthy nutrition and increase in the number of chronic diseases. In this study, dried dietary species of microalga, Chlorella vulgaris, and cyanobacterium Spirulina platensis were hydrolyzed with pancreatin enzyme to obtain protein hydrolysates. The hydrolysis yield of biomass was 55.1 ± 0.1 and 64.8 ± 3.6% for C. vulgaris and S. pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 31 publications
2
30
1
Order By: Relevance
“…To destroy the cells, homogenization under pressure or enzymatic hydrolysis was used, followed by ultrafiltration/diafiltration. Kose et al [ 58 ] obtained protein hydrolysates from the microalgae Chlorella vulgaris, Chlorella cyanobacterium and Spirulina platensis and evaluated their digestibility in in vitro experiments. The studied hydrolysates showed rather high digestibility values and low cytotoxicity.…”
Section: Microalgae Proteins Extraction Methodsmentioning
confidence: 99%
“…To destroy the cells, homogenization under pressure or enzymatic hydrolysis was used, followed by ultrafiltration/diafiltration. Kose et al [ 58 ] obtained protein hydrolysates from the microalgae Chlorella vulgaris, Chlorella cyanobacterium and Spirulina platensis and evaluated their digestibility in in vitro experiments. The studied hydrolysates showed rather high digestibility values and low cytotoxicity.…”
Section: Microalgae Proteins Extraction Methodsmentioning
confidence: 99%
“…Several authors have previously reported that A. platensis biomass shows 10% to 20% higher IVDMD [17,74] and up to 50% higher IVPD [32] than C. vulgaris biomass. The different IVDMD and IVPD values between A. platensis and C. vulgaris biomass are probably related to differences in cell wall structure, considering that while cyanobacteria have thin cell walls composed by peptidoglycan, green algae such as C. vulgaris have thick and rigid cellulosic cell walls [75].…”
Section: In Vitro Digestibilitymentioning
confidence: 97%
“…Biofertilizer products derived from algae are obtained from biosecure species, which do not produce toxins or allergens, guaranteeing in this manner, not only the safety of the operators but also of the food fertilized with these products. Because of its biological origin, biofertilizers derived from algae do not contravene any of the assumptions of organic production, and they do represent an alternative for quality production (da Silva Ferreira and Sant'Anna, 2017; Kose et al, 2017;Rossi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%